Influence of Selected Parameters on Ash Particle Trajectories When Modelling Deposition on Superheater Tubes in Pulverised Coal Boilers Using Fluent Code - Wacławiak Krzysztof; Kalisz Sylwester (Chemical and Process Engineering)
Widely used CFD codes enable modelling of PC boilers operation. One of the areas where these numerical simulations are especially promising is predicting deposition on heat transfer surfaces, mostly superheaters. The basic goal of all simulations is to determine trajectories of ash particles in the vicinity of superheater tubes. It results in finding where on the surface the tube will be hit by particles, and what diameter and mass flow of the particles are. This paper presents results of CFD simulations for a single tube and a bundle of in-line tubes as well. It has been shown that available parameters like ash particle density, shape factor, reflection coefficients affect the trajectories in a different way. All the simulations were carried out with Fluent code of Ansys software.